The case for decreased surgeon-reported complications due to surgical volume and fellowship status in the treatment of geriatric hip fracture: An analysis of the ABOS database. - Taylor D Ottesen; Michael R Mercier; Jordan Brand; Michael Amick; Jonathan N Grauer; Lee E Rubin (PLoS ONE, 2022)
Introduction American orthopaedists are increasingly seeking fellowship sub-specialization. One proposed benefit of fellowship training is decrease in complications, however, few studies have investigated the rates of medical and surgical complications for hip fracture patients between orthopedists from different fellowship backgrounds. This study aims to investigate the effect of fellowship training and case volume on medical and surgical outcomes of patient following hip fracture surgical intervention. Methods 1999-2016 American Board of Orthopedic Surgery (ABOS) Part II Examination Case List data were used to assess patients treated by trauma or adult reconstruction fellowship-trained orthopedists versus all-other orthopaedists. Rates of surgeon-reported medical and surgical adverse events were compared between the three surgeon cohorts. Using binary multivariate logistic regression to control of demographic factors, independent factors were evaluated for their effect on surgical complications. Results Data from 73,427 patients were assessed. An increasing number of hip fractures are being treated by trauma fellowship trained surgeons (9.43% in 1999-2004 to 60.92% in 2011-2016). In multivariate analysis, there was no significant difference in type of fellowship, however, surgeons with increased case volume saw significantly decreased odds of complications (16-30 cases: OR = 0.91; 95% CI: 0.85-0.97; p = 0.003; 31+ cases: OR = 0.68; 95% CI: 0.61-0.76; p<0.001). Femoral neck hip fractures were associated with increased odds of surgical complications. Discussion Despite minor differences in incidence of surgical complications between different fellowship trained orthopaedists, there is no major difference in overall risk of surgical complications for hip fracture patients based on fellowship status of early orthopaedic surgeons. However, case volume does significantly decrease the risk of surgical complications among these patients and may stand as a proxy for fellowship training. Fellows required to take hip fracture call as part of their training regardless of fellowship status exhibited decreased complication risk for hip fracture patients, thus highlighting the importance of additional training.